Clinical manifestations of 17 patients affected with mucopolysaccharidosis type VI and eight novel ARSB mutations. Issue 6 (27th March 2014) - Kantaputra, Piranit Nik; Kayserili, Hulya; Guven, Yeliz; Kantaputra, Warissara; Balci, Mehmet C.; Tanpaiboon, Pranoot; Tananuvat, Napaporn; Uttarilli, Anusha; Dalal, Ashwin
<x xml:space="preserve">Abstract</x> Mucopolysaccharidosis (MPS) type VI or Maroteaux‐Lamy syndrome is a very rare autosomal recessive lysosomal storage disease, caused by a deficiency of the enzyme N‐acetylgalactosamine‐4‐sulfatase (Arylsulfatase B, ARSB). Clinical examination, biochemical studies, and molecular genetic analyses have been performed in 17 patients affected with MPS VI from 15 unrelated families from Thailand, India, and Turkey. Large ear lobule appears to be a newly recognized finding of this syndrome. Mutation analysis of the ARSB gene revealed seven missense and three frameshift mutations of which eight were novel. Novel missense mutations were p.Asp53Asn, p.Val376Glu, p.Glu390Lys, p.Pro445Leu, and p.Trp450Cys, while an Indian patient was homozygous for two novel missense mutations (p.Pro445Leu and p.Trp450Cys). Three novel frameshift mutations were p.Pro70fsX123, p.Ser403fs, and p.Thr526fs. Two previously reported mutations, p.Arg160Gln and p.Leu321Pro, were also observed in our cohort. The amino acid Arg160 appears to be the mutational hot spot for the ARSB gene. Five patients homozygous for p.Leu321Pro mutation had early onset of the disease, and haplotype analysis showed that the mutation is a founder mutation in Turkish population © 2014 Wiley Periodicals, Inc.